2017
DOI: 10.4172/2167-0277.1000271
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of Oral Negative Pressure Therapy for Obstructive Sleep Apnea-Hypopnea Syndrome

Abstract: Background: Although the continuous positive airway pressure is the gold standard therapy for patients with moderate to severe obstructive sleep apnea-hypopnea syndrome (OSAHS), there are several treatment options such as mandibular advancement devices, tongue-retaining devices, and nasal airway stent devices. Recently, newly developed intraoral pressure gradient therapy system, iNAP ® Sleep Therapy System, was introduced as an alternative treatment for OSAHS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…One study suggested the use of the iNAP device for the treatment of mild-to-moderate OSA. 11 In an investigation of the therapeutic spectrum of the iNAP device, Hung et al (2020) reported that the best candidates for its use are individuals without obesity and with a baseline AHI between 5 and 50 events/h. 12 The discrepancies in our study results indicated that neither the AHI nor BMI can be a favorable predictor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One study suggested the use of the iNAP device for the treatment of mild-to-moderate OSA. 11 In an investigation of the therapeutic spectrum of the iNAP device, Hung et al (2020) reported that the best candidates for its use are individuals without obesity and with a baseline AHI between 5 and 50 events/h. 12 The discrepancies in our study results indicated that neither the AHI nor BMI can be a favorable predictor.…”
Section: Discussionmentioning
confidence: 99%
“…8 Oral pressure therapy (OPT) is an alternative treatment modality for patients with poor compliance to CPAP. [9][10][11][12][13] Nigam et al 10 reported that the OPT success rate (defined as a reduction of ≥50% from the baseline apnea-hypopnea index [AHI] and a post-OPT treatment residual AHI of ≤10) varies between 25% and 37%. However, the success rate does not correlate with OSA severity or the body mass index (BMI); 10,12 therefore, identifying responders and nonresponders to OPT treatment necessitates the establishment and comprehensive examination of predictors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation